DAYA TARIK ENDORSERNOAH TERHADAP BRAND IMAGEIKLAN KARTU XL - Retnaningtyas, Ester; Hastasari, Chatia; Pratiwi, Dyah Retno (KOMUNITAS, 2014)
Nowadays,Â almostÂ allÂ ofÂ televisionÂ commercialsuseartistsasendorser.Â TheÂ endorserÂ isÂ selected basedÂ onÂ its attraction.Â TheyÂ has a duty inintroducing theÂ brandÂ ofÂ a product. XL is one of the advertisement which use artist as an endorser. XL uses NOAH as an endorser because NOAH is considered having capability in creating brand image XL. The success in building the brand image is also determined by consumer perceptions of endorser who became icon is in the advertisement. Therefore, this research focus on analysis of is there any influence of NOAH attraction to brand imageÂ ofÂ XLÂ advertisementÂ amongÂ SahidÂ SurakartaÂ UniversityÂ studentÂ classÂ 2011. The populationsÂ of thisÂ study is allof students inclass 2011Â atÂ SahidÂ SurakartaÂ University.Â TheÂ total number of student is 295. Where as, the sampling techniques was used a simple random sampling (the taking of sample from population was randomlyÂ without regard to the existing strata in the population). This research used respondenceâs questionnaire as the primary data. Meanwhile, in analizingÂ influenceÂ ofÂ NOAHÂ attractionÂ toÂ brandÂ imageÂ ofÂ XLÂ advertisementÂ amongÂ Sahid SurakartaÂ UniversityÂ studentÂ classÂ 2011Â wasÂ useÂ Rank-OrderÂ Correlation.Â TheÂ ResultsÂ ofÂ this studyshows that results Spearmens coefficient Rho=0.426 and p-value of 0.000. Thus,p-value less thanÂ 0.05Â itÂ means thatÂ there is significant influence of NOAHÂ attraction toÂ brand imageÂ of XL advertisement among Sahid Surakarta University student class 2011.